The Correlation Between Low Birth Weight And Stunting Incidence In Balet Baru Village, Sukowono District, Jember Regency - Rachmawati, Dwita Aryadina; Normasari, Rena; Nurmaida, Eny; Hakiim, Arsyzilma; Sudarmanto, Yohanes; Parti, Dita Diana; Sofiana, Kristianningrum Dian; Astuti, Ida Srisurani Wiji; Putri, Elvia Rahmi Marga; Sulihah, Nurfaizah Titisari (International Journal of Health and Information System, 2025)
Stunting is an indicator of chronic nutritional disorders and is still a complex public health problem. One of the direct risk factors for stunting is Low Birth Weight (LBW). This study is an analytical observational study that aims to determine the correlation between the history of Low Birth Weight (LBW) and the incidence of stunting in toddlers. The research was carried out in Balet Baru Village, Sukowono District, Jember Regency. The population in this study were all children aged 6 months to 5 years who are recorded in the Maternal and Child Health (KIA) register in Balet Baru Village. The total number of research subjects was 168 toddlers in a case-control design. Bivariate analysis is used to determine the relationship between LBW history and stunting incidence using the Chi-Square test. The results of the analysis showed a p-value of 0.002 (p < 0.05), which means that there is a statistically significant correlation between the history of LBW and the incidence of stunting in children aged 6 months to 5 years. An odds ratio (OR) value of 4.640 shows that children with a history of LBW have a 4.64 times greater risk of stunting than children without a history of LBW.